Pengaruh Gaya Belajar Siswa terhadap Keaktifan Belajar Siswa pada Mata Pelajar IPS di SMP Negeri 9 Kubung - Rahmatika, Desi; Putri, Desi Armi Eka; Basyirun, Fajri (YASIN, 2024)
This research is motivated by the low active learning participation of students in Social Studies at SMP Negeri 9 Kubung. It is suspected that this is due to the students' lack of understanding of their learning styles, making it difficult for them to grasp and comprehend the lessons effectively. The aim of this study is to determine how much influence students' learning styles have on their active learning in Social Studies at SMP Negeri 9 Kubung. In this research, the researcher used a quantitative approach. The population of the study consisted of all students enrolled in SMP Negeri 9 Kubung in the 2024/2025 academic year, totaling 40 students. The sample was taken using the total sampling technique, as the sample included all elements of the population. The analysis technique used was simple linear regression analysis. The results of the study showed that the students' learning style (X) had a significance level of 0.000 < 0.05 and a t-value of 7.558 > t-table value of 2.024, indicating that the alternative hypothesis (Ha) is accepted and the null hypothesis (H0) is rejected. Based on the results, it can be concluded that there is a positive and significant influence of students' learning styles on their active learning in Social Studies at SMP Negeri 9 Kubung. The influence of the learning style variable (X) on tactive learning variable (Y) is 60.1%.